Actual and Forecasted Vulnerability Assessment to Seawater Intrusion via GALDIT-SUSI in the Volturno River Mouth (Italy) - Gianluigi Busico; Carla Buffardi; Maria Margarita Ntona; Marco Vigliotti; Nicolò Colombani; Micòl Mastrocicco; Daniela Ruberti (Remote Sensing, 2021)
Coastal areas have become increasingly vulnerable to groundwater salinization, especially in the last century, due to the combined effects of climate change and growing anthropization. In this study, a novel methodology named GALDIT-SUSI was applied in the floodplain of the Volturno River mouth for the current (2018) and future (2050) evaluation of seawater intrusion accounting for the expected subsidence and groundwater salinization rates. Several input variables such as digital surface model, land use classification, subsidence rate and drainage system have been mapped via remote sensing resources. The current assessment highlights how areas affected by salinization coincide with the semiperennial lagoons and inland depressed areas where paleosaline groundwaters are present. The future assessment (2050) shows a marked increase of salinization vulnerability in the coastal strip and in the most depressed areas. The results highlight that the main vulnerability driver is the Revelle index, while predicted subsidence and recharge rates will only slightly affect groundwater salinization. This case study indicates that GALDIT-SUSI is a reliable and easy-to-use tool for the assessment of groundwater salinization in many coastal regions of the world.